Radio resource allocation for coordinated multi-point systems - Batista, Rodrigo Lopes (2011)
The International Telecommunications Union (ITU) established through the International Mobile Telecommunications (IMT)-Advanced a set of requirements for high performance of 4th Generation (4G) communication systems and, with the aim of meeting such requirements, 3rd Generation Partnership Project (3GPP) Long Term Evolution (LTE) is considering a set of enhancements, referred to as LTE-Advanced. In the LTE-Advanced context, Coordinated Multi-Point (CoMP) communication appears as a promising technology to boost system throughput and to allow for an efficient Radio Resource Allocation (RRA). CoMP systems promise very high performance in terms of spectral efficiency and coverage benefits when perfect Channel State Information (CSI) is available at the transmitter. However, perfect CSI is difficult to obtain in CoMP systems due to an increased number of channel parameters to be estimated at the receiver and to be fed back to the transmitter. So, the performance of such systems is compromised when the CSI is not perfectly known during CoMP processing, which is an important problem to be addressed. Space Division Multiple Access (SDMA) grouping algorithms are usually employed in order to find a suitable set of users for spatial multiplexing. The largest SDMA group is not always the best group in a given data transmission such that higher gains might be achieved by dynamically adjusting the SDMA group size. Besides, algorithms that balance the Signal to Interference-plus-Noise Ratio (SINR) among different links might ensure a certain level of link quality and so provide a more reliable communication for the scheduled users. This master thesis provides system-level analyses for RRA algorithms that exploit coordination in the downlink of CoMP systems to implement adaptive resource reuse and so improve system throughput. Herein, RRA strategies which consider dynamic SDMA grouping, joint precoding and power allocation for SINR balancing are studied in CoMP systems assuming imperfect CSI in order to obtain a better approximation with regard to the real-world implementations. It is shown through system-level analyses that quite high throughput gains are achieved through intelligent RRA. In conclusion, the results show that Sequential Removal Algorithms (SRAs) and SINR balancing provide system spectral efficiency gains. However, a critical degradation on the performance of these RRA strategies due to imperfect CSI is also shown.